Critical analysis of an accident and emergency ward. Issue 5 (September 1996) - Rainer, T H; Swann, I J; Crawford, R
Abstract : OBJECTIVES: To describe the work, both qualitatively and quantitatively, of an accident and emergency (A&E) ward, and discuss some of the advantages and disadvantages associated with this ward. METHODS: An observational study was carried out of all patients admitted to the A&E ward of Glasgow Royal Infirmary from 1 January 1992 to 31 December 1992. Epidemiological and management data were collected for all patients admitted. RESULTS: There were 2460 admissions, of which 69% were related to trauma and 45% to head injury; 47% of the patients had consumed alcohol before admission. Accidental trauma was the commonest reason for admission (57%), followed by assault (33%). Ninety two per cent of admissions stayed for less than 3 d, but 33% of the workload was spent on a small number of patients admitted for longer than 7 d. CONCLUSIONS: This A&E ward presents a significant workload, and some of its most serious problems lie with those patients who stay longer than 72 h. The safe and effective use of the ward depends upon it being well resourced, along with the department it serves.